Desmin and αB-crystallin interplay in maintenance of mitochondrial homeostasis and cardiomyocyte survival - Antigoni Diokmetzidou; Elisavet Soumaka; Ismini Kloukina; Mary Tsikitis; Manousos Makridakis; Aimilia Varela; Constantinos H. Davos; Spiros Georgopoulos; Vasiliki Anesti; Antonia Vlahou; Yassemi Capetanaki (2016)
The association of desmin with αΒ-crystallin, and the fact that mutations in either one of them lead to heart failure in humans and mice, suggests a potential compensatory interplay between them in cardioprotection. To address this hypothesis, we investigated the consequences of αΒ-crystallin overexpression in the desmin deficient (des-/-) mouse model, which possesses a combination of the pathologies found in most cardiomyopathies, with mitochondrial defects as a hallmark. We demonstrated that cardiac specific αΒ-crystallin overexpression ameliorates all these defects and significantly improves cardiac function to almost wild type levels. Protection by αΒ-crystallin overexpression is linked to maintenance of proper mitochondrial protein levels, inhibition of abnormal mitochondrial permeability transition pore activation and maintenance of mitochondrial membrane potential (Δψ). Furthermore, we found that both desmin and αΒ-crystallin are localized at SR-mitochondria associated membranes, where they interact with VDAC, Mic60, the core component of MICOS (mitochondrial contact site and cristae organizing system) complex and ATP synthase, suggesting that these associations could be crucial in mitoprotection at different levels.